R&D internationalization strategies of the world's top corporate R&D investors - Heike Belitz; Anna Lejpras (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper contributes to the debate on the internationalization of the R&D activity of multinational enterprises (MNEs). Specifically, we examine the following research questions: (1) What are the determinants of the MNEs' R&D internationalization level? (2) What types of internationalization strategies - home-base-augmenting (HBA), home-base-exploiting (HBE), technology-seeking (TS), and/or market-seeking (MS) - do the MNE employ? and (3) What are the typical patterns in pursuing different strategy mixes by MNEs? To this end, we merge data on 2,000 global research leaders from the 2012-2014 period with the EPO Worldwide Patent Statistical Database PATSTAT. Based on the final dataset, covering about 1,700 world's top corporate R&D investors and their patenting activity, we find that about one-fifth focus their patent-relevant R&D activity in their home country only. Our study confirms former results of the literature that R&D offshoring is used by leading R&D performers predominantly to acquire complementary technological knowledge (HBA strategy) and to use their home-based technological advantages to expand their market penetration (HBE strategy). With patent data from the late 2010s, we find a further increase in the proportion of HBA strategies compared to the 2000s. This indicates the growing importance of international knowledge exchange between technologically similarly oriented locations. Hence, the increased attraction of foreign R&D locations is no reason for concern regarding the perceived hollowing-out of the national innovation systems. Indeed, since the advantages built at home are at the core of both the HBA and HBE strategies, the national system of innovation in the home country should support the technological advantages of firms, thereby enabling them to succeed in their R&D activity abroad.
Keywords: F23; O19; O31; O32; 330; R&D; patents; innovation; internationalization; multinational firms; global firms